Remember me : [large type] a Spanish Civil War novel - Escobar, Mario, 1971- (Center Point Large Print, 2021)
"From international bestseller Mario Escobar comes a 20th-century historical novel of tragedy and resilience inspired by Spain's famed Children of Morelia and the true events that shaped their lives"--